Programmable Universal Filter and Quadrature Oscillator Using Single Output Operational Transconductance Amplifiers - Montree Kumngern (Informacije MIDEM - Journal of Microelectronics Electronic Components and Materials, 2021)
This paper presents a new programmable universal filter and quadrature oscillator based on single output operational transconductance amplifiers (OTAs). The proposed universal filter and quadrature oscillator can be achieved into single topology by programming using analog switches. When the circuit programs as a universal filter, it can realize low-pass, high-pass, band-pass, band-stop and all-pass filters with orthogonal and electronic controls of the natural frequency and the quality factor. When the circuit programs as a quadrature oscillator, it provides three-phase quadrature output signals which the condition of oscillation and the frequency of oscillation can be controlled orthogonally and electronically. The proposed structure can be realized based on single output OTAs which is easily implemented both commercially available integrated circuits as OTAs and complementary metal-oxide semiconductor and bipolar junction transistor OTA as IC forms. The performance of the proposed circuit is investigated by SPICE simulation using standard 0.18 μm CMOS process and experiment test using LM13600 discrete component integrated circuit as OTAs is used to confirm the workability of the new circuit.
Keywords: Analog and Mixed-Signal Circuit Design; Sensor Technology and Measurement Systems; Advanced MEMS and NEMS Technologies